What is the postoperative nutrition intake in children with congenital heart disease? A single-center analysis in China - Ping Ni; Mingjie Zhang; Yibei Wu; Wenyi Luo; Zhuoming Xu (BMC Pediatrics, 2022)
Abstract Background It is common that inadequate nutritional intake happens in patients with congenital heart disease (CHD), which can adversely affect the prognosis of patients. However, the details and reasons are not clear enough so far. Therefore, the primary aim of this study was to investigate the current nutritional requirements and energy intake on days 1–7 in the cardiac intensive care unit after surgery. Our secondary aim was to investigate potential factors that hinder nutritional supply and to compare the resting energy expenditure (REE) based on two methods, the Fick method and the Schofield equation. Methods Using retrospective analysis, we collected data from postoperative children with CHD at a children's hospital in Shanghai, China. We used the Fick method to calculate the REE, and compare the results with the actual enteral nutrition intake. Meanwhile, we recorded the initiation time of enteral nutrition, feeding intolerance, unfinished milk volume, etc. Then the correlation between the results of the Fick method and the equation method was calculated. Results A total of 49 patients were included, with a median age of 22 months (IQR 4.9, 57.3), and a median Aristotle basic complexity score of 8 (IQR 6.0, 9.8). The time interval for surgical intervention within 7 days after operation was 4 (IQR 2.5, 6). No statistical difference in REE on postoperative days 1–7. The average enteral nutrition energy provided 64.6 (33.6, 79.6)% of the REE, which showed a significant decrease on postoperative day 4, and then reached its lowest on postoperative day 5. The protein supply was 0.7 ± 0.3 kcal/kg/d. In addition, the REE calculated by the Fick method was moderately correlated with that estimated by the equation (r = 0.467, P = 0.001). Conclusions The energy and protein supply in the acute postoperative period in children with CHD is inadequate. Fluid restriction and fasting may be the main causes. In addition, there is a moderate correlation between the REE calculated by the Fick method and that estimated by the equation.